Utilization of PPT Media as a Creative Solution for PAI Teachers in Conveying the Example of the Prophet in Grade Sdit Insan Cermat Bandung City - Maslani; Muhammad Alif Ramadhan; Sahrul Fadil; Taufik Agung Nugraha; Hani Rolis Aliyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
Abstract This study is motivated by the importance of Islamic Religious Education in shaping the character of elementary school students, particularly in the topic of the exemplary character of Prophet Muhammad (peace be upon him), which is often less effective when delivered through conventional lecture methods. This study aims to analyze the use of PowerPoint media as a creative solution for Islamic Religious Education teachers in conveying the values of honesty, trustworthiness, responsibility, and noble character to fourth-grade students at SDIT Insan Cermat Kota Bandung. The theoretical framework used in this study includes the Cognitive Theory of Multimedia Learning, Social Constructivism Theory, and Social Learning Theory. This study employs a qualitative approach with a descriptive-analytical method. Data were collected through observation, interviews, and documentation studies, and were then analyzed through data reduction, data display, and conclusion drawing. The findings indicate that PowerPoint helps improve students’ attention, understanding, emotional engagement, and internalization of the exemplary values of Prophet Muhammad. This medium is effective when teachers are able to design slides that are simple, visual, interactive, and meaningful for students’ learning experiences. Keywords: Islamic Education, PowerPoint Media, Prophet Exemplarity.